(untitled) (Journal of Hama University, 2020)
The experiment was carried out at Abi-Jarash farm- Faculty of Agriculture/ Damascus University during seasons 2018-2019. in order to study the effect of two concentrations of auxin (IAA) (25, 50 ppm) and two concentrations of zinc (ZnSo4) (0.5, 1 g.l-1) on some vegetative growth, flowering and yield charactaristics of strawberry cv. Festival. The experiment was designed as completely randomized blocks design with three replicates, each experimental unit contain ten plants. The results showed the positive effect of auxin (IAA) and zinc (ZnSo4) foliar application on improving the physiological and quality parameters of the strawberry plant. However, the treatment with auxin at 50 ppm supplemented with zinc at 1 g.l-1 increased leaf concentration of nitrogen and potassium (2.53, 1.75 % respectively), chlorophyll b (1.44 mg/g fresh weight), weight and fruits length (18.05 g and 3.95 cm respectively) comparing with other treatments and control. However, the treatment with auxin at 50 ppm supplemented with zinc at 0.5 g.l-1 increased relative water content (92.37 %), leaf concentration of chlorophyll a and carotene (3.64, 1.09 mg/g fresh weight respectively), phosphorus (0.52 %) comparing with other treatments and control. The results also exhibited that the treatment with auxin at 25 ppm supplemented with zinc at 1 g.l-1 was the best treatment in improved, fruits diameter (3.37 cm).